Objectively-assessed and self-reported sedentary time in relation to multiple socioeconomic status indicators among adults in England: a cross-sectional study. Issue 11 (5th November 2014) - Stamatakis, Emmanuel; Coombs, Ngaire; Rowlands, Alex; Shelton, Nicola; Hillsdon, Melvyn
Abstract : Objectives: To examine the associations between socioeconomic position (SEP) and multidomain self-reported and objectively-assessed sedentary time (ST). Design: Cross-sectional. Setting: General population households in England. Participants: 2289 adults aged 16–96 years who participated in the 2008 Health Survey for England. Outcomes: Accelerometer-measured ST, and self-reported television time, non-television leisure-time sitting and occupational sitting/standing. We examined multivariable associations between household income, social class, education, area deprivation for each SEP indicator (including a 5-point composite SEP score computed by aggregating individual SEP indicators) and each ST indicator using generalised linear models. Results: Accelerometry-measured total ST and occupational sitting/standing were positively associated with SEP score and most of its constituent SEP indicators, while television time was negatively associated with SEP score and education level. Area-level deprivation was largely unrelated to ST. Those in the lowest composite SEP group spent 64 (95% CIs 52 to 76) and 72 (48 to 98), fewer minutes/day in total ST and occupational sitting/standing compared to those in the top SEP group, and an additional 48 (35–60) min/day watching television (p<0.001 for linear trend). Stratified analyses showed that these associations between composite SEP score and total ST were evident only among participants who were in employment. Conclusions: Occupational sitting seems to drive the positive association between SEP and total ST. Lower SEP is linked to higher TV viewing times.